HUBUNGAN PENGETAHUAN DAN SIKAP REMAJA TERHADAP TINGKAT KEJADIAN FLOUR ALBUS DI DESA LEBAK WANGI RT/RW 007/007 KABUPATEN TANGERANG - Sahpitri, Sahpitri; Solihati, Solihati; Sari, Rina Puspita (Nusantara Hasana Berdikari, 2022)
1 between 20 teenagers in the world experience vaginal discharge every year. The number of women in the world in 2013 was 6.7 billion people and around 75% had experienced vaginal discharge. And it was found that 5 out of 10 teenagers in RT/RW 007/007 did not know about vaginal discharge and how to deal with it. Research objective to determine the relationship between knowledge and attitudes of adolescents on the incidence of flour albus in Lebak Wangi Village, RT/RW 007/007, Tangerang Regency. This type of research is descriptive analytic with cross sectional approach, total sampling technique with 40 respondents, statistical test used chi square. Based on the results of the chi square test, the P value is 0.036 <0.05, which means that there is a significant relationship between knowledge of flour albus and the incidence of flour albus. While the results of the chi square test, the P value is 0.000 <0.05, which means that there is a significant relationship between adolescent attitudes and the incidence of flour albus. Â There is a relationship between knowledge of flour albus and the incidence of flour albus. And there is a relationship between adolescent attitudes and the incidence of flour albus.